THE ROLE OF THE RELIEF IN THE DEVELOPMENT OF HUMAN SETTLEMENTS IN HUŞI DEPRESSION - Elena CHIRILĂ - ACATRINEI (Studia Universitatis Babeş-Bolyai: Geographia, 2015)
The Role of the Relief in the Development of Human Settlements in Huşi Depression. Human settlements are closely related to the regional physical-geographical framework determined by the geological, geomorphological, hydrological and climatic features that condition the location and evolution of the settlements system. Among the morphometric parameters that characterize local conditions, slopes and altitudes play an important role in the spatial extent of settlements. Slope determines the access, the extension of built space and the drainage inside the area of settlements. An excessively flat land is not able to drain rainwater. The optimum gradient is 1-20, a value that generally characterizes terraces, plateaus and sculptural interfluves or accumulation glacises. Slopes over 50 raise problems in the construction of buildings and access roads, especially on territories with an excessive fragmentation. The altitudinal gradient is also important in the spatial development of settlements, as it implies a significant contrast between the localities situated in the eastern lower part of Depression and those located on the higher western and northern sides. To analyze the spatial evolution of human settlements in the Huşi Depression in relation to slope and altitude were used various editions of cartographic materials covering a period of about 80 years (1920-2010), the years 1950 and 2010 being conventionally selected as reference.